Barriers to trade union participation among universities staff - Ismail, Fadillah; Rahmat, Anis Wajihah (Journal of Islamic, Social, Economics and Development, 2026)
Trade unions provide a collective voice for employees through representation and collective bargaining, yet participation among Malaysian university staff remains modest. Drawing on a focused literature-based synthesis in the public university context, this paper consolidates the main barriers that suppress union membership and engagement. Evidence points to persistent information deficits and weak workplace communication about union roles, often reinforced by limited exposure and intergenerational communication gaps. Individual-level deterrents, such as growing individualism, competing work and family responsibilities, and low perceived relevance, interact with concerns about union influence and effectiveness, reducing willingness to participate. Participation is further constrained by structural and institutional factors, including indirect organisational resistance that discourages union activities and dilutes collective voice. The synthesis highlights that improving participation requires clearer value communication, modernised union strategies aligned with contemporary staff concerns, and trust-building engagement through transparent governance and constructive union–management dialogue.